2023
DOI: 10.4038/ijabf.v9i1.135
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study on the Relationship Between Credit Rating and Banks´ Performance: Evidence from an Emerging Market

A. Abu-Alkheil,
G. Khartabiel,
A. Riaz
et al.

Abstract: This paper provides new empirical evidence with respect to the influence of banks´ long- and short-term credit ratings and their volatility performance in the emerging market of Pakistan covering 10-year analysis and a unique and comprehensive data set derived from a sample of Islamic and conventional banks with Islamic windows. The purpose of this paper is to examine the nature of the relationship between Islamic banks´ performance and banks´ credit rating focusing on the emerging market of Pakistan over the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…However, Belanès et al (2015) reported a negative impact of the global financial crisis of 2007–2008 on the efficiency of Islamic banks in the GCC region, similar to their conventional peers worldwide. Moreover, Abu-Alkheil et al (2017) find that “CBs grant a higher percentage of loans than their benchmark peers and are more profitable in the pre-, during- and post-crisis periods. Additionally, in the post-crisis period, IBs held more liquidity and experienced a slower recovery.…”
Section: The Risk-taking Behavior and Stability Frameworkmentioning
confidence: 99%
“…However, Belanès et al (2015) reported a negative impact of the global financial crisis of 2007–2008 on the efficiency of Islamic banks in the GCC region, similar to their conventional peers worldwide. Moreover, Abu-Alkheil et al (2017) find that “CBs grant a higher percentage of loans than their benchmark peers and are more profitable in the pre-, during- and post-crisis periods. Additionally, in the post-crisis period, IBs held more liquidity and experienced a slower recovery.…”
Section: The Risk-taking Behavior and Stability Frameworkmentioning
confidence: 99%
“…These banks differ significantly from conventional banks in various ways, such as regulations, profit distribution (Farook et al , 2012), asset-backed product offerings (Cerovic et al , 2017) and capital formation (Abu-alkheil et al , 2017). The Islamic banking system adheres to the laws of Islamic Shari'ah, making interest-free banking (Abbass et al , 2022a, 2022b, 2022c; Hassan et al , 2017; Hassan et al , 2022a, 2022b; Hassan et al , 2021; Zaher and Hassan, 2001).…”
Section: Introductionmentioning
confidence: 99%